Patient-centred care and quality of life and hope among Japanese patients receiving home medical care: a multicentre, cross-sectional study - Nobuhiro Ikeda; Michiko Hinata; Noriaki Kurita; Tomoka Nakamura; Takashi Fujii; Chihiro Tsuchiya; Yukio Tsugihashi; Hidekazu Iida; Shinu Hayashi; Masakazu Yasunaka; Misaki Hirose; Yutaka Shirahige; et al. (BMJ Open)
Objectives Patient-reported outcomes reflecting quality of life (QOL) and hope are essential targets for in-home medical care. This study examined the association between the quality of patient-centred care and both QOL and hope.Design Multicentre, cross-sectional study.Setting Twenty-nine home care clinics in the Tokyo Metropolitan Area, Nara Prefecture and Nagasaki Prefecture in Japan.Participants 200 patients receiving home medical care.Exposure Patient-centredness was measured using the Japanese version of the Primary Care Assessment Tool-Short Form (JPCAT-SF).Outcome measures The primary outcome measures were QOL, assessed using the QOL-Home Care (QOL-HC) scale, and hope, measured using the Health-Related Hope (HR-Hope) scale. Mixed-effects linear models were applied.Results A higher JPCAT-SF total score was associated with a higher QOL-HC score (adjusted mean difference per 10-point increase: 0.28, 95% CI 0.16 to 0.40). Among the JPCAT-SF domains, higher scores in first contact (0.16, 95% CI 0.08 to 0.23), longitudinality (0.20, 95% CI 0.11 to 0.29), comprehensiveness (services available) (0.12, 95% CI 0.03 to 0.20), comprehensiveness (services provided) (0.08, 95% CI 0.01 to 0.15) and community orientation (0.11, 95% CI 0.02 to 0.20) were also associated with higher QOL-HC scores. Similarly, a higher JPCAT-SF total score was associated with a higher HR-Hope score (adjusted mean difference per 10-point increase: 4.8, 95% CI 2.9 to 6.7). Additionally, higher scores in individual JPCAT-SF domains were associated with higher HR-Hope scores: first contact (2.7, 95% CI 1.3 to 4.1), longitudinality (2.5, 95% CI 0.8 to 4.2), coordination (1.2, 95% CI 0.2 to 2.3), comprehensiveness (services available: 1.8, 95% CI 0.5 to 3.2; services provided: 1.3, 95% CI 0.4 to 2.3) and community orientation (1.8, 95% CI 0.5 to 3.1).Conclusions Higher quality patient-centred care is positively associated with enhanced QOL and hope among home medical care patients. Patient-centredness should be strengthened in daily clinical practice.